Combatting malnutrition in Niger through courtyard gardens - Bramsen, Nathan (Kansas State University, 2015)
We live on a planet where every three point six seconds, a life is taken from starvation or malnutrition (Millennium Development Goals, 2005). One epicenter of this tragedy is Kwara Tagi, Niger in Africa. Superficial fixes seem to leave the infrastructure of such a place in greater shambles than the original condition. The focus of this work addresses the question, “What is the potential for significantly reducing malnutrition in Kwara Tagi through sustainable intervention using Moringa trees in courtyard gardens in a manner accessible to all, without dependence on outside resources, while providing an outlet for new economic opportunity?” Rather than artificially attempting to sustain life, this work researches, articulates and suggests the potential found in a simple and strategic path of implementing Moringa trees in courtyards for the purpose of eradicating malnutrition and providing new economic opportunities. Requiring little initial funding and using resources that already exist and are not currently being utilized, this approach empowers the local people without creating any dependency on outside intervention. Furthermore, this plan would provide an economic boost to families, increase community capital, begin the reversal of desertification, work towards eradicating malnutrition, all while engaging youth in envisioning the possibilities surrounding them.
Keywords: Malnutrition; Moringa; Niger; Courtyard gardens; Sustainable development; Agronomy (0285)